Bhuwo Nāch: A Multifaceted Ritual Performance of Sudurpaschim - Joshi, Pusp Raj (Far Western Review, 2023)
This paper aims to explore the multifaceted theatrical performativity of ritualistic Bhuwo Nāch on the occasion of Bhuwo Parva. To reflect on the performative diversity of this dance, the researcher has observed the performance during the festival, especially in Bajhang. Bhuwo Nāch is a traditional folk dance of the people dwelling in hilly regions, especially in Bajhang, Achcham, Bajura, and Doti districts of Sudurpaschim Province of Nepal. The research is based on participant observation, interviews, and focus group discussion. The findings of the study show that Bhuwo Nāch is a ritual performative folk dance which imparts diverse facets of social interaction, religio-cultural performance, regional identity, oral tradition, fits of valorous display and tactics of survival against the natural odds and human intolerance. The dance is performed to carry ritual significance through theatrical performance, shape social identity, display valorous community standing, reveal social reality, maintain harmony among the community people, give continuity to cultural orality, and enhance survival strategy.